Application of the Audit in Ecuador's MyPEs: A study of the demand - Quispe Fernández, Gabith Miriam (2016)
The audit is an issue addressed and applied in Public and Private Enterprises, large or small regulated and not by control bodies in the Republic of Ecuador. Small and Medium Enterprises (SMEs) are not obliged, do not apply, because a large percentage of them are personal, family or corporate companies, do not have an organizational structure, accounting and adequate procedures for financial and administrative control. The objective of the research is to identify the factors that determine the application of the audit in the MSEs from the determination of the voluntary demand for an audit. The descriptive, analytical and statistical method is used, through the bibliographic review and the binary linear regression to data of the last National Survey to Companies with their establishments and Microenterprise. It is shown that H1. The application of a financial and management audit is measured by the obligation to keep accounting and is associated with the legal nature and cost of the service of an audit; Y, H2. If the audit is not mandatory then it is necessary that the regulatory institutions and the university play the motivating role. It is concluded that there is a probability of hiring audit services voluntarily because it helps the achievement of the objectives and serves as an important element for the manager in making decisions and having the certainty of the financial situation and the reality of the business based In the conclusions and recommendations of the audit report based on the findings and value judgments issued by the auditor.